Comparative effectiveness of glatiramer acetate and interferon beta formulations in relapsing–remitting multiple sclerosis. (August 2015) - Kalincik, Tomas; Jokubaitis, Vilija; Izquierdo, Guillermo; Duquette, Pierre; Girard, Marc; Grammond, Pierre; Lugaresi, Alessandra; Oreja-Guevara, Celia; Bergamaschi, Roberto; Hupperts, Raymond; Grand'Maison, Francois; Pucci, Eugenio; et al.
Background: The results of head-to-head comparisons of injectable immunomodulators (interferon β, glatiramer acetate) have been inconclusive and a comprehensive analysis of their effectiveness is needed. Objective: We aimed to compare, in a real-world setting, relapse and disability outcomes among patients with multiple sclerosis (MS) treated with injectable immunomodulators. Methods: Pairwise analysis of the international MSBase registry data was conducted using propensity-score matching. The four injectable immunomodulators were compared in six head-to-head analyses of relapse and disability outcomes using paired mixed models or frailty proportional hazards models adjusted for magnetic resonance imaging variables. Sensitivity and power analyses were conducted. Results: Of the 3326 included patients, 345–1199 patients per therapy were matched (median pairwise-censored follow-up was 3.7 years). Propensity matching eliminated >95% of the identified indication bias. Slightly lower relapse incidence was found among patients treated with glatiramer acetate or subcutaneous interferon β-1a relative to intramuscular interferon β-1a and interferon β-1b ( p ≤0.001). No differences in 12-month confirmed progression of disability were observed. Conclusion: Small but statistically significant differences in relapse outcomes exist among the injectable immunomodulators. MSBase is sufficiently powered to identify these differences and reflects practice in tertiary MS centres. While the present study controlled indication, selection and attrition bias, centre-dependent variance in data quality was likely.